Don't Think That Kids Aren't Noticing: Indirect Pathways to Children's Fear of COVID-19 - Radanović, Ana; Micić, Isidora; Pavlović, Svetlana; Krstić, Ksenija (Frontiers in Psychology, 2021)
The present study is couched within Rachman’s three-pathway theory of fear acquisition (Rachman 1977, 1991). Besides the direct contact with the objects of fear, this model also includes two indirect pathways to fear acquisition: negative information transmission and modelling. The study aims to explore the contribution of these three factors to the level of children’s fear of COVID-19. The sample consisted of 376 children (59.6% girls), aged 7 to 19 (Mage = 12.77 SDage = 3.57), and one of their parents (Mage = 42.88, SDage = 6.00). The survey was conducted online during the COVID-19 national state of emergency in the Republic of Serbia. The children assessed their fear of COVID-19, general fearfulness, negative information transmission and modelling by their parents, as well as the level of exposure to negative information outside their home. The parents assessed their own fear of COVID-19 and trait anxiety. Parents’ anxiety, children’s age, and children’s general fearfulness were used as covariates. The results of our path analysis provide support for Rachman’s notion of indirect pathways. The more the parents were afraid of COVID-19, the more they expressed this (either verbally or through their behaviour), which in turn led to an increase in the children’s fear of COVID-19. Furthermore, children’s exposure to negative information related to COVID-19, provided by their teachers and peers or stemming from the media, directly contributed to the level of children’s fear. The results of the study emphasize the importance of caregivers’ behaviour during global health crises and provide some clues as to what caregivers may do to protect their children’s mental health in such circumstances.